Tracking tracer motion in a 4‐D electrical resistivity tomography experiment. Issue 5 (26th May 2016) - Ward, W. O. C.; Wilkinson, P. B.; Chambers, J. E.; Nilsson, H.; Kuras, O.; Bai, L.
Abstract: A new framework for automatically tracking subsurface tracers in electrical resistivity tomography (ERT) monitoring images is presented. Using computer vision and Bayesian inference techniques, in the form of a Kalman filter, the trajectory of a subsurface tracer is monitored by predicting and updating a state model representing its movements. Observations for the Kalman filter are gathered using the maximally stable volumes algorithm, which is used to dynamically threshold local regions of an ERT image sequence to detect the tracer at each time step. The application of the framework to the results of 2‐D and 3‐D tracer monitoring experiments show that the proposed method is effective for detecting and tracking tracer plumes in ERT images in the presence of noise, without intermediate manual intervention. Key Points: Saline tracer motion tracked in 2‐D and 3‐D time‐lapse experiments Plume detection and assignment using Kalman filter predict/update process Resistivity images effective for autonomous detection and tracking of tracer plumes